Природа бифокального очага землетрясения и предвестники удара - Николаевский, В.Н.; Собисевич, Л.Е. (Геофизический журнал, 2015)
На основі принципу витіснення надлишкових об'ємів і використання натурних даних запропоновано біфокальну модель вогнища землетрусу, що включає зони дилатансії і компакції. Перша відповідає визначеному набору передвісників, а друга компенсує зміни об'єму тріщин. Джерела радону оконтурюють зону дилатансії (початок зростання тріщин). Гіпоцентр головного удару знаходиться в перехідній зоні. Існування двох фокусів у вогнищі землетрусу підтверджено експериментально на підставі гравіметричних даних і спостереженнями за рівнем поверхні океану. On the base of ousting principle and application of the data on location bifocal model of earthquake source is proposed, which includes zones of dilatancy and compaction. The first one corresponds to the recognized set of precursors and the second one compensates the changes of the fissures volume. The sources of radon delineate dilatancy zone (the beginning of fissures growth). Hypocenter of the main blow is in the transitional zone. Existence of two foci in the source of earthquake is confirmed experimentally on the base of gravity data and observations of the ocean surface level. Anomalous magnetic disturbances in variations of magnetic field of the Earth are being analyzed, which can be considered as a short-term precursor. This type of disturbances is inseparably connected with tectonomagnetic effects in lithosphere and other geo-spheres. The data of experimental observations of magnetic disturbances-precursors have been presented, which allow to draw a conclusion that they are induced by internal sources located in the lower geo-spheres of the Earth.